Tantangan Tenaga Pendidik dalam Menyeimbangkan Edukasi Tradisional dan Media Berbasis Deep Learning di Raudhatul Athfal - Zahroti Musanif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Digital transformation in early childhood education, particularly within the Raudhatul Athfal (RA) environment, has brought a significant paradigm shift in teaching methods and learning media. This article qualitatively explores the challenges faced by educators in integrating deep learning-based media and artificial intelligence into a curriculum historically dominated by traditional approaches. Based on an analysis of the Decree of the Minister of Religious Affairs (KMA) Number 347 of 2022 concerning the Guidelines for the Implementation of the Merdeka Curriculum in Madrasas, this study highlights institutional autonomy in creating learning innovations relevant to 21st-century competencies. Findings indicate that although deep learning-based media offers adaptive personalization and enhanced cognitive engagement through the pillars of mindful, meaningful, and joyful learning, its implementation is hindered by low digital literacy among educators, infrastructure constraints such as limited internet access and hardware, and theological dilemmas regarding the teacher's role as a spiritual guide. This article also compares the impact of both methods on the six aspects of child development in the Child Development Achievement Standards (STPPA), concluding that a hybrid approach balancing digital stimulation with traditional social-physical interaction is the most effective strategy to achieve well-being in accordance with the principles of maqāṣid al-syarī'ah. This balancing act is crucial to ensuring holistic child development without neglecting the values of akhlakul karimah that characterize RA